(untitled) (Journal of Bio-Science, 2021)
The present experiment was carried out in the household ponds (0.04 to 0.08 ha in area with 1.3 to 2.4 m in depth) of small indigenous people at Barind Tract region, northwest Bangladesh during September, 2017 to June, 2018 to know the growth performance of bivalve with carp. Two different treatments with 3 replicates were used, in treatment one (T1) only the carp polyculture was performed and in treatment two (T2) carp and bivalve polyculture was performed. Good quality of carp fingerlings (Labeo rohita, Gibelion catla, Cirrhinus cirrhousus, Hypophthalmichthys molitrix and Ctenopharyngodon idella) and freshwater bivalve (Lamellidens marginalis) seeds were stocked in the ponds. Stocking density and size of the seeds were similar for all of the study ponds. During the experiment there were no significant differences was observed in growth performance of the fishes between the two different treatments (p<0.05). The weight gain was recorded for L. rohita 420.31 g in T1 and 436.25 g in T2, for G. catla 237.01 g in T1 and 329.66 g in T2, for C. cirrhosus 263.53 g in T1 and 301.74 g in T2, for H. molitrix 559.6 g in T1 and 593.57 g in T2, for C. idella 510.11 g in T1 and 619.57g in T2. The weight gain of L. marginalis was 12.3 g in T2. During this experiment the production of carp was recorded 2524.5 kg/ha in T1 and 2618.2 kg/ha in T2 and the bivalve production was 1284.4 kg/ha in T2. This study is the first report on growth performance of bivalve with carp in the Barind Tract region of northwest Bangladesh. The result of this study will be helpful for the development of bivalve aquaculture in this climatically vulnerable region. J. Bio-Sci. 29(2): 99-110, 2021 (December)